Immigration and Mental Health - Alegría, Margarita (Curr Epidemiol Rep, 2017)
PURPOSE OF REVIEW: While the experience of migration and resettlement in a new country is associated with mental health risks, immigrants generally demonstrate better mental health than expected. This review describes patterns in mental health outcomes among immigrants. We discuss a conceptual model of the potential underlying mechanisms that could buffer the stress and disadvantage experienced by this substantial and growing population. RECENT FINDINGS: While epidemiological studies have established a general pattern of lower risk for mental health disorders among first-generation (foreign-born) immigrants in the U.S., recent studies highlight how this pattern varies substantially by the intersection of race, ethnicity, national origin, gender, and socioeconomic status. Contextual factors including the family and neighborhood context; an immigrant’s social position; experiences of social support and social exclusion; language competency and ability; and exposure to discrimination and acculturative stress further influence the relationship between immigration and mental health. SUMMARY: We conclude with an emphasis on social resilience processes, with a focus on how immigrants develop social relations, social capital and social networks. We recommend future directions for research that prioritize identifying and understanding social adaptation strategies adopted by immigrant groups to cope with immigration stressors.